Performance of the cooperatives in the City of Iloilo - Alonzo, Josie; Cornites, Armilyn P.; Ilaya, Erjune E.; Tabanda, Emilio G. (1999.)
This descriptive study attempted to find out the factors that likely contribute to the success of cooperatives in the City of Iloilo. The independent variables included member's involvement, types of services and trainings of officers and members. The dependent variable was the success of cooperatives. Forty-six (46) cooperatives in the city of Iloilo provided the necessary data, which were then, analyzed using the univariate analysis and the mode as the statistic. Results showed that member's involvement is relevant to the success of the cooperatives (95.7%). In addition, success of these cooperatives is related to the leadership trainings and seminars which the officers and members have undergone (97.8%). On the other hand, people's membership in a cooperative depends on the type of services which the cooperative offers (100%). These results revealed that these cooperatives are performing just right and are considered successful.
Research Study (Mgt 200 - Management Research) -- [Iloilo City, University of the Philippines in the Visayas-College of Management], October 1999.